The Effect Of Brain Gym On Cognitive Function In The Elderly In Banjar Belaluan Sadmerta Dangin Puri Kauh Village North Denpasar District - Ni Putu Diah Anantari; I Putu Astrawan; Komang Tri Adi Suparwati (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
The aging process will cause a decrease in the neurological system which will affect cognitive function in the elderly. The purpose of this study was to determine the effect of brain gym on cognitive function in the elderly in Banjar Belaluan Sadmerta, Dangin Puri Kauh Village, North Denpasar District. Experimental research with a pre-test and post-test control group design which was carried out in April - May 2022 with a research sample of 16 subject in Banjar Belaluan Sadmerta who met the inclusion criteria. The measurement instrument to assess cognitive function was using the Mini Mental State Examination (MMSE) questionnaire. The data were analyzed by independent t-test to determine the effect of brain gym on cognitive function in the elderly and the results obtained p = 0,000 (p <0,05) which indicates that there is a significant difference between the cognitive function of the elderly in the treatment group and the control group. It was concluded that brain gym affects cognitive function in the elderly in Banjar Belaluan Sadmerta, Dangin Puri Kauh Village, North Denpasar District